Biomarker-based analysis of preclinical progression in spinal and bulbar muscular atrophy. (24th April 2018) - Hijikata, Yasuhiro; Hashizume, Atsushi; Yamada, Shinichiro; Inagaki, Tomonori; Ito, Daisuke; Hirakawa, Akihiro; Suzuki, Keisuke; Atsuta, Naoki; Tsuboi, Takashi; Hattori, Makoto; Hori, Akihiro; Banno, Haruhiko; et al.
Abstract : Objective: To identify a candidate biomarker reflecting biological changes during the preclinical progression of spinal and bulbar muscular atrophy (SBMA). Methods: We analyzed longitudinal changes in biochemical parameters obtained during health examinations before and after the diagnosis of SBMA. We estimated trajectories of clinical markers across years from the onset of weakness using linear mixed models and compared these trajectories with those estimated for male healthy controls and patients with amyotrophic lateral sclerosis (ALS) and Parkinson disease (PD). Moreover, we examined the relationship between serum creatinine level and the onset of symptoms using Kaplan-Meier curves. Results: Between October 2014 and October 2017, we enrolled 40 patients with genetically confirmed SBMA, 48 healthy controls, 25 patients with ALS, and 20 patients with PD. In patients with SBMA, we evaluated the patients' data for a period of 17.3 ± 7.5 years, including 11.4 ± 7.1 years of preclinical phase. Decreases in serum creatinine occurred >10 years before the onset. The mean serum creatinine concentration was 0.56 mg/dL at the onset of weakness in patients with SBMA compared to 0.88 ± 0.10 mg/dL on final evaluation in healthy controls. Serum levels of alanine transaminase and aspartate transaminase showed tendencies to increase in preclinical SBMA. These preclinical changes of biomarkers were not observed in either ALS or PD. Conclusions: Our findings suggest that serum creatinine begins to decrease before the onset of clinical symptoms and is a biomarker for disease progression and the efficacy of therapeutics in preclinical SBMA.